History and Journalism: interrelations among disciplines - Eiroa, Matilde (Historia y Comunicación Social, 2014)
This study tries to analyse the possible rapprochement among History and Journalism in order to guess what new knowledge we could get with its interrelationship. Both disciplines come from different conceptual, epistemological and methodological perspectives but it is our interest to deepen in ties, beyond the known boundaries of the object of study. We introduce issues related to the reorganization of the social and human sciences, with the proposal of similar methodologies and the encouragement of interdisciplinary.
Keywords: History; Journalism; interdisciplinary; Current History; Journalism History.